The Role Of Endogenous Proteolytic Enzymes In The Production Of Budu - Ng, Yen Fen (2011)
The objective of this study was to determine whether the transformation of fish protein during budu fermentation was caused by endogenous enzymes or exogenous enzymes produced by microorganism present in the viscera and the muscles of the fish. Malaysian fish sauce, budu was produced by incubating a mixture of anchovies (Encrasicholina punctifer) and salt in a ratio of 3:1. Four types of treatment were carried out on the fish: i.e. whole, un-irradiated fish as the control (budu C); whole, 10 kGy gamma irradiated fish (budu R); eviscerated, un-irradiated fish (budu E), and eviscerated, 10 kGy gamma irradiated fish (budu A). Proteolytic activity was significantly higher in budu prepared from whole, un-eviscerated fish (C) compared to budu prepared from whole but irradiated fish (R). There was no difference (P>0.05) in proteolytic activity in budu prepared from both eviscerated, irradiated (A) and eviscerated and un-irradiated fish (E). Inhibition studies showed that the predominant proteases in budu prepared from whole and irradiated (R) fish and whole and un-irradiated (C) is trypsin-like protease belonging to the serine protease family. Low inhibition by pepstatin A and EDTA on protease in budu indicates the lack of involvement of aspartic protease and metalloprotease in the budu production. Low proteolytic bacterial counts in all budu suggested that proteolytic bacteria plays; only a minor role in the protein hydrolysis of fish. Using the API system, Bacillus, Staphylococcus and, Micrococcus were identified as the proteolytic bacteria in all budu samples.